Developing Aboriginal and Torres Strait Islander cultural indicators: an overview from Mayi Kuwayu, the National Study of Aboriginal and Torres Strait Islander Wellbeing - Sarah C. Bourke; Janet Chapman; Roxanne Jones; Makayla-May Brinckley; Katherine A. Thurber; Bianca Calabria; Kate Doery; Anna Olsen; Raymond Lovett (BMC, 2022)
Abstract Background For Aboriginal and Torres Strait Islander peoples, culture is foundational to health and wellbeing. However, its inherent conceptual complexity and diversity across and within different Aboriginal and Torres Strait Islander cultural groups means that it has rarely been explored in depth by epidemiological research. As a result, there are very few measures which adequately represent the heterogeneity and importance of Aboriginal and Torres Strait Islander cultures for health and wellbeing. Tools grounded in the social determinants of health are mostly based on European academic opinion about what constitutes culture and wellbeing, and the views of Indigenous peoples are rarely included. Mayi Kuwayu, the National Study of Aboriginal and Torres Strait Islander Wellbeing, developed a new survey tool based on health and wellbeing as perceived by Aboriginal and Torres Strait Islander people. This paper describes several of the key processes used to identify cultural domains and develop questionnaire items for the survey tool, reflecting the importance of culture to Aboriginal and Torres Strait Islander peoples. Methods Focus groups were conducted at community organisations and conferences with Aboriginal and Torres Strait Islander people. These sessions were aimed at identifying key cultural domains to be addressed by the Mayi Kuwayu questionnaire and to field test drafts of the questionnaire, which were then modified according to focus group feedback and expert input. Results Extensive community consultations allowed us to identify key cultural domains, generate questionnaire items, and test initial content validity. The six overarching cultural domains identified during the development of the Mayi Kuwayu questionnaire were: Connection to Country; Beliefs and knowledge; Language; Family, kinship, and community; Cultural expression and continuity; and Self-determination and leadership. Conclusions The processes used by Mayi Kuwayu have generated meaningful cultural items for use in Aboriginal and Torres Strait Islander health and wellbeing research. Further assessment of these processes, including a comparison with best practice guidelines and psychometric testing of the items and scales developed, will be conducted in a future program of work.